2010
DOI: 10.1007/s00775-010-0648-8
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of enantiomeric complexes [PtCl2L2] (L2 is aromatic bisphosphanes and aromatic diamines)

Abstract: Enantiomeric complexes of formula [PtCl(2)L(2)] [L(2) is (R)-(+)-BINAP and (S)-(-)-BINAP, where BINAP is 2,2'-bis(diphenylphosphane)-1,1'-binaphthyl, and (R)-(+)-DABN and (S)-(-)-DABN, where DABN is 1,1'-binaphthyl-2,2'-diamine], were tested for their cytotoxic activity against three cancer cell lines and for their ability to bind to the human telomeric sequence folded in the G-quadruplex structure. Similar experiments were carried out on prototypal complexes cisplatin and cis-[PtCl(2)(PPh(3))(2)] for comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 64 publications
3
31
1
Order By: Relevance
“…[5,6] Similar observations were also reported for a Pt-O-alkyldithiocarbonato series of complexes. [17] A similar activity on cisplatin-resistant cell lines was observed very recently for a series of cis-[PtP 2 S 2 ] pharmacophores (where P 2 refers to two monodentate or one bidentate phosphane ligand and S 2 is a dithiolato ligand), suggesting that these compounds will undergo specific activation within the cellular environment, with possible breaking of Pt-S or Pt-P bonds. The coordination of the second functional group may occur after halide abstraction, in organic solvents, with silver salts.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…[5,6] Similar observations were also reported for a Pt-O-alkyldithiocarbonato series of complexes. [17] A similar activity on cisplatin-resistant cell lines was observed very recently for a series of cis-[PtP 2 S 2 ] pharmacophores (where P 2 refers to two monodentate or one bidentate phosphane ligand and S 2 is a dithiolato ligand), suggesting that these compounds will undergo specific activation within the cellular environment, with possible breaking of Pt-S or Pt-P bonds. The coordination of the second functional group may occur after halide abstraction, in organic solvents, with silver salts.…”
Section: Introductionsupporting
confidence: 68%
“…[17] Only when ring-closure is hampered by the presence of an imide functionality (as in O4), the hydrolysis of which would require harsh conditions, is the O form preserved. However, the -COOfunctionality in the C forms require very low pH to be protonated to give the corresponding more active O forms, therefore this intramolecular ligand rearrangement does not operate under physiopathologic conditions, as verified by the biological inactivity of complexes C3 and C5 on monolayer human tumour cell cultures.…”
Section: Discussionmentioning
confidence: 99%
“…As the cellular platinum accumulation has been described to be exponentially related to the lipophilicity of the compounds, it was assumed that the two enantiomers have similar uptake, which is higher than that of both cisplatin and oxaliplatin [82]. Similar to findings by Bombard and colleagues [81], later work indicated that the CDDPrGB cells are not cross-resistant to neither S -[Pt(DABN)Cl 2 ] nor R -[Pt(DABN)Cl 2 ] [80]. Based on the IC 50 values, S - and R -[Pt(DABN)Cl 2 ] were determined to be more active compared to cisplatin in both GUMBUS and CDDPrGB cells [80].…”
Section: Alternative Pathways For Accumulation Of Cisplatinmentioning
confidence: 97%
“…S - and R -[Pt(DABN)Cl 2 ] were investigated for the first time by Bombard et al, who demonstrated that the two enantiomers are able to overcome cisplatin resistance in human ovarian A2780 and colorectal HCT116 cell lines [81]. Furthermore, they demonstrate that the S-isomer seemed to be more potent than the R -isomer [81].…”
Section: Alternative Pathways For Accumulation Of Cisplatinmentioning
confidence: 99%
See 1 more Smart Citation